STAGES OF IMPLEMENTING IEME AND CLIL METHODOLOGIES IN SECONDARY AND HIGHER EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the stages of implementing International EnglishMedium Education (IEME) and Content and Language Integrated Learning (CLIL) methodologies in secondary and higher education institutions. The study highlights the pedagogical significance of these approaches, their implementation mechanisms, and their impact on learners’ academic competence and English language proficiency. The research demonstrates that a phased and systematic introduction of IEME and CLIL enhances both subject knowledge and academic language skills, preparing learners for global education and professional environments.